Firm Performance and Corporate Sustainability Performance Management: The Mediating Effect of Investors’ Reliability towards Companies listed on the Market for Alternative Investment (MAI) - Oonprechavanich, Thanet (Journal of Management Science Nakhon Pathom Rajabhat University, 2023)
This research aimed to analyze direct and indirect effects of variables influencing the corporate sustainability performance management. The model consisted of 3 latent variables, namely firms’ performance as cause variable, investors’ reliability as mediator variable, and the effect variable as the corporate sustainability performance management of companies listed on the Market for Alternative Investment (MAI). This research was the survey research testing 125 respondents from entrepreneurs in Market for Alternative Investment (MAI). The research samples were obtained from stratified random sampling. The data was collected by questionnaire. In this study, Partial least squares structural equation modeling (PLS-SEM) technique was used for hypothesis testing. According to the analysis found that (1) the firm’s performance had a direct effect on the investors’ reliability and the corporate sustainability performance management of companies listed on MAI were equal to 0.820 and 0.311 respectively (2) the investors’ reliability had a direct effect on the corporate sustainability performance management of companies listed on MAI was equal to 0.595 and (3) the firm’s performance had indirect effect on the corporate sustainability performance management of companies listed on MAI by passing through the investors’ reliability was equal to 0.488. Article history: Received 10 March 2023 Revised 25 April 2023 Accepted 27 April 2023 SIMILARITY INDEX = 3.39 %